An expanded role for the mining sector in Australian society? - Measham, T.; McKenzie, Fiona Haslam; Moffat, K.; Franks, D. (EContent Management Pty Ltd, 2013)
Questions over the role of mining in the Australian economy and society have gained increasing public scrutiny in recent years. In this paper we consider whether the role of mining in Australian society has changed with the recent mining boom. The paper draws attention to four key areas. The first is the economics of mining, where a rise in commodity values has made mining more profitable. Mining now dominates Australian exports more than in previous booms. The second area is the scale of mining operations, which have grown substantially, reflecting unprecedented investment. The third area is the degree to which the effects of resource extraction extend to surrounding areas and distant urban centres through long distance commuting. Finally, we consider the centrality of the mining sector in public life: attention to mining in the media and encroachment on other land uses, and we look for evidence of changes in public acceptance of the sector. In conclusion we argue that the role of the mining sector in Australian society and economy has indeed changed. The changes in terms of trade and the scale of mining have made the resource sector so important in Australia that increased impact in public life is unavoidable.